Development of Independence-Based Entrepreneurship Textbook - Imam Mashudi (AL-ISHLAH: Jurnal Pendidikan, 2025)
Entrepreneurship education in Indonesia remains underdeveloped, leading to a lack of independence among graduates in pursuing entrepreneurial careers. Enhancing learning methods through entrepreneurship education is essential to developing students' skills and competitiveness. The Creative Product and Entrepreneurship Learning initiative is one approach to fostering students' ability to create innovative products, which is critical for entrepreneurial success. This study aimed to develop and evaluate entrepreneurship textbooks for university students to facilitate independent learning. The Dick and Carey model was employed in the textbook development process, and the study was conducted with students from Bina Mandiri University Gorontalo. Data were collected through practical use evaluations, effectiveness assessments, and statistical analysis using the Wilcoxon Signed Ranks Test. Findings indicate that the developed textbook was highly practical, achieving an average practicality score of 87.43%. The effectiveness assessment also showed a high effectiveness rate of 85.90%. Statistical analysis using the Wilcoxon Signed Ranks Test revealed a significant improvement in students' post-test scores after using the textbook (Asymp. Sig. 0.05, p = 0.002). The results demonstrate that the entrepreneurship textbook effectively supports independent learning and enhances students' entrepreneurial competencies. The significant improvement in post-test results suggests its potential for broader application in entrepreneurship education. Future research should explore further refinements and assess long-term impacts on graduates' entrepreneurial success.